The Effect of Target Practice Training Program on Backhand Shot Accuracy of Sumedang Squash Athletes - Luthfi Fadilah; Encep Sudirjo; Dinar Dinangsit (Tadulako Journal Sport Sciences And Physical Education, 2026)
Backhand shot accuracy is an essential component of performance in squash, particularly in maintaining rally consistency and creating scoring opportunities during matches. However, conventional training methods are often less effective in helping athletes maintain shot precision under high-intensity playing conditions. Target practice training was implemented as a focused exercise method to improve technical precision and movement consistency during backhand execution. This study aimed to examine improvements in backhand shot accuracy through target practice training in junior squash athletes using the Hunt Squash Accuracy Test (HSAT). A quantitative approach with a one-group pretest-posttest experimental design was employed. The sample consisted of 15 regional-level athletes. The intervention program was conducted over eight weeks with a frequency of two training sessions per week, each lasting 120 minutes and including 30 minutes of high-intensity target-based training. Data were analyzed using descriptive statistics, paired-sample t-tests, and N-Gain analysis. The results showed a significant increase in the mean accuracy score from 30.53 (SD = 2.13) to 48.53 (SD = 1.84), with p < 0.05. The N-Gain value of 0.72 indicated a high level of improvement, while the effect size analysis demonstrated a strong intervention effect. These findings suggest that target practice training is effective in improving backhand shot accuracy and may be considered as an alternative technical training method for junior squash athletes.